Freshwater algae of North America : ecology and classification - Wehr, John D.; Sheath, Robert G.; Kociolek, John Patrick (London : Academic Press, 2015)
Freshwater Algae of North America: Ecology and Classification, Second Edition is an authoritative and practical treatise on the classification, biodiversity, and ecology of all known genera of freshwater algae from North America. The book provides essential taxonomic and ecological information about one of the most diverse and ubiquitous groups of organisms on earth. This single volume brings together experts on all the groups of algae that occur in fresh waters (also soils, snow, and extreme inland environments). In the decade since the first edition, there has been an explosion of new information on the classification, ecology, and biogeography of many groups of algae, with the use of molecular techniques and renewed interest in biological diversity. Accordingly, this new edition covers updated classification information of most algal groups and the reassignment of many genera and species, as well as new research on harmful algal blooms.
3 . Picoplanktonic and Nanoplanktonic Species4 . Benthic and Epiphytic Species; 5 . Transported Plankton in Rivers and Streams; 6 . Wetlands; D . Extreme Environments; 1 . Thermal Waters; 2 . Saline Inland and Coastal Habitats; 3 . Endolithic and Lithogenic Habitats; E . Geographic Distribution; IV . Collection, Preparation, and Culture; V . Key and Description of Genera; A . Key; B . Descriptions of Genera 2 ; Gloeobacterales; Gloeobacteraceae; Synechococcales; Synechococcaceae; Merismopediaceae; Coelosphaeriaceae; Chamaesiphonaceae; Chroococcales; Microcystaceae; Aphanothecaceae.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Freshwater algae -- Ecology -- North America; Freshwater algae -- North America -- Classification; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; Algues d'eau douce -- {u2163}ologie -- Amique du Nord; Freshwater algae -- Ecology -- North America; Freshwater algae -- North America -- Classification; Freshwater algae; Freshwater algae -- Ecology; North America; Electronic books; Electronic books; Classification